Combined effects of Rhodiola rosea and caffeine supplementation on aerobic endurance and muscle explosiveness: a synergistic approach - Yun, Hezhang; Lu, Bin; Su, Wenbo; Wang, Junjie; Zheng, Jing; Wang, Jing; Wang, Zhaolong; Li, Yi; Sun, Yaowei; Liu, Chang (Frontiers in Nutrition, 2024)
This study examined the synergistic effects of combining Rhodiola rosea (RHO) and caffeine (CAF) supplementation on muscle endurance and explosiveness in SD rats and human subjects, encompassing individuals without prior exercise training experience and seasoned aerobic athletes. Male SD rats and healthy human volunteers were randomly divided into four groups: CAF, RHO, CAF+RHO, and a control group (CTR). Nutritional supplements were administered throughout the training period, and pre-and post-measurement data were collected. In both the rat model and human subjects, the RHO+CAF group demonstrated significantly greater effects compared to the use of RHO or CAF supplements individually. Rats in the RHO+CAF group demonstrated extended running and swimming times and an increase in erythropoietin (EPO) mRNA expression in comparison to the CTR. Blood parameters, such as serum EPO levels, were enhanced in the CAF+RHO group, while blood urea nitrogen (BUN) and lactate (LA) levels significantly decreased in both the RHO and CAF+RHO groups. Hepatic and muscle glycogen contents were also higher in these groups. The gene expression analysis in rats demonstrated an elevation in the mRNA levels of glucose transporter-4 (GLUT-4), peroxisome proliferator-activated receptor γ coactivator-1 alpha (PGC-1α), Monocarboxylate transporter 1 (MCT-1), and Heme Oxygenase-1 (HO-1) in both the RHO and RHO+CAF groups. For individuals without prior aerobic training experience, the RHO+CAF group showed significant improvements compared to the CTR group in maximal oxygen consumption (VO2max), 5 km run, countermovement jump (CMJ), standing long jump, and 30m sprint. For individuals with years of aerobic training experience, the RHO+CAF group exhibited enhanced performance in the 5 km run, 设置了格式: 下标 CMJ, and standing long jump compared to the CTR group. In conclusion, the continuous 30-day supplementation of RHO, combined with a single dose of CAF, demonstrated superior effects on muscle endurance and explosiveness in both animal and human studies when compared to the use of RHO or CAF individually.